Professional orientation theory and practice development in the Lithuanian SSR - Kregzdė, S. (Psichologija, 1968)
Shortly after the First World War, theoretical research and practical professional guidance activity was begun; they were terminated during the German occupation. Due to a succession of objective and subjective reasons, they were renewed only in the last decade. Since 1957, a string of sociological psychological research has been conducted demonstrating students' professional interests and inclinations relative to national economic needs, the knowledge-based validity of students' professional self-determination, i.e. medical and psychological requirements, as well as the nature of a profession. Significant discrepancies were disclosed.Based on this data as well as overall school experience and analysis of teaching plans, much pedagogical research was carried out using pedagogical experiment and eight-year schools 7th-8th grade leaders' professional guidanceSystems were created. Research work intensified practical activity (professional information, professional consultation), which was set up to coordinate the Interdepartmental Council of Students Professional Guidance of the Republic. The Council includes the planning organs of Education and Higher and Secondary Specialized Education Ministries, the Committee on Vocational-technical education, health care, the press, radio and television, as well as research institutes and university department representatives.Further professional guidance work aims to closely link with research work: the high and mid-level qualified specialist professional guidance is set up in an effort to select special secondary and higher education establishments with existing professional interests and inclinations; also, professional guidance effectiveness is determined.
Keywords: professional orientation; professional choice; professional guidance